Demonstration Examination in the System of Secondary Vocational Education as a New Format of Competence Assessment of Future Elementary School Teachers - Elina Yakovleva; Galina Voiteleva; Irina Krasilova (ARPHA Proceedings, 2019)
One of relevant problems of vocational education modernization is quality improvement of training. In this regard, the introduction of new competence-focused formats of educational results assessment, which will be able to realize the nature of independent assessment and meet the requirements of educational and professional standards, acquires special relevance. A new format of assessment of educational results meeting all these requirements is the demonstration examination based on standards of assessment of general and professional competences within the international competitions WorldSkills. The article focuses on the development of the system of independent assessment of future primary school teachers’ qualification with the help of the demonstration examination held with the use of control and measuring materials of the National WorldSkills Russia Championships on Competence R21 Primary School Teaching. Moscow Region as an associated partner of the WorldSkills Russia movement suggested this competence and the State University of Humanities and Technology (the city of Orekhovo-Zuyevo, Moscow region) developed the Technical Description of the competence and the strategy of implementing the demonstration examination in this competence in the system of secondary vocational education. The growing number of educational institutions in different parts of the country using now the demonstration examination as a new format of educational results assessment proves that the demonstration examination has got mass support of regions in the Russian Federation.